Emotional Intelligence (Journal of Parents and Teachers, 2024)
The article discusses emotional intelligence and the importance of self-awareness in recognizing feelings, problems, and experiences, as well as the best ways to face them daily. It also includes a series of questions with answers based on studies and insights about impulses and the significance of good self-control in problem-solving and developing social skills.
Keywords: emotional; intelligence; impulses; self-awareness; feelings